THE EFFECT OF "HENS" APPLICATION (HEALTHY EMOTIONAL FREEDOM TECHNIQUE OF STROKE PATIENTS) ON THE STRESS LEVEL OF POST STROKE PATIENTS - Widyawati, Ika Yuni; Dewi, Ni Luh Putu Thrisna; Wati, Ni Made Nopita; Liem, Khatijah (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2024)
Introduction: Stroke is  characterized  by neurological deficits resulting fromacute focal injury to  the central nervous system, originating from blood vessels such as cerebral infarction, cerebral hemorrhage and subarachnoid hemorrhage. Stress is a known trigger for  stroke and  various  therapies are available to manage  stress. This study explores the effectiveness of a mind body therapy, specifically the HENS application on Android in reducing stress in post stroke patients.Method: The study employs a  quasi-experimental  design with a pre-test and post-test  with control group. The sampling technique in the study was  convenience sampling with a sample size of 48 post-stroke patients (24 for each intervention and control group). Data was collected using the DASS questionnaire and the HENS application.Results: The results revealed significant changes in stress levels before and after the six-day intervention with the  HENS Application. The intervention group showed a p value=0.000 indicating a significant reduction in stress levels. In contrast,  the control group’s  p value  was 0.853, suggesting  no significant change without treatment.Conclusions: The HENS application has the potential to provide post-stroke patients with independent support for managing stress. It offers clear and useful guidelines for implementing HENS techniques which can improve confidence of post stroke patients in independently managing stress.